2020
DOI: 10.37190/epe200302
|View full text |Cite
|
Sign up to set email alerts
|

Generalized modeling of the sludge volume index and suspended solids to monitor activated sludge bioflocculation using image analysis

Abstract: The performance of an activated sludge wastewater treatment plant depends on bioflocculation that is monitored by physical measurements such as the sludge volume index (SVI) and mixed liquor suspended solids (MLSS). The estimation of SVI and MLSS has been proposed using image analysis based modeling which is time-efficient and valid for multiple plants operating in different states. The methodology includes the sequence of image acquisition using bright-field microscopy, a robust segmentation of flocs, partiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The performance of the WWTP can be monitored by the sludge volume index (SVI) and the mixed liquor suspended solids (MLSS) (Khan et al, 2020). The MLSS concentration in the aeration tank directly determines the solids loading rate to the final clarifier, which makes it a very important operating parameter (James et al, 2015).…”
Section: Analysis Of Mlss and Svi In Activated Sludgementioning
confidence: 99%
“…The performance of the WWTP can be monitored by the sludge volume index (SVI) and the mixed liquor suspended solids (MLSS) (Khan et al, 2020). The MLSS concentration in the aeration tank directly determines the solids loading rate to the final clarifier, which makes it a very important operating parameter (James et al, 2015).…”
Section: Analysis Of Mlss and Svi In Activated Sludgementioning
confidence: 99%
“…Experiments showed that the microscopic characteristics of the effluent could evaluate the working state of the sludge and the effluent quality of the wastewater. Beyond using integrated microscopic features of the wastewater image, Khan et al [9] suggested using fewer microscopic features to reduce the complexity of the calculation. For example, without relying on the characteristics of filamentous bacteria, only the floc size was used to analyze the sludge settling performance.…”
Section: Introductionmentioning
confidence: 99%